2003
DOI: 10.1523/jneurosci.23-17-06956.2003
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Huntingtin-Associated Protein-1 Causes Neuronal Death Resembling Hypothalamic Degeneration in Huntington's Disease

Abstract: Huntington's disease (HD) is caused by a polyglutamine expansion in the disease protein huntingtin. The polyglutamine expansion causes huntingtin to interact abnormally with a number of proteins. However, it is unclear whether, and how, huntingtin-associated proteins are involved in the neurodegeneration in HD. Here, we show that huntingtin-associated protein-1 (HAP1), which is involved in intracellular trafficking of epidermal growth factor receptor (EGFR), is highly expressed in the hypothalamus. Mice lackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
161
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(167 citation statements)
references
References 52 publications
5
161
0
1
Order By: Relevance
“…The highest P/S ratio of Hap1 was seen in the hypothalamus (Fig. 1B), in agreement with the finding that SBs are more abundant in the hypothalamus than in other tissues (5,10,14). Thus, these results showed that the use of a detergent-based strategy to enrich SBs in mouse brain was feasible.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The highest P/S ratio of Hap1 was seen in the hypothalamus (Fig. 1B), in agreement with the finding that SBs are more abundant in the hypothalamus than in other tissues (5,10,14). Thus, these results showed that the use of a detergent-based strategy to enrich SBs in mouse brain was feasible.…”
Section: Resultssupporting
confidence: 89%
“…DYRK1A is a major candidate gene for DS and likely is responsible for selective DS phenotypes. To look for DS symptoms that could be related to the regulation of DYRK1A on the Dcaf7-Hap1 interaction, we focused on growth retardation, which is a cardinal feature of DS (56) and is the most noticeable phenotype in Hap1-KO mice (5,10). Both individuals with DS and Hap1-KO mice exhibit impaired growth velocity after birth; the difference, however, is that in DS, growth velocity is most reduced between 6 mo and 3 y of age (56,57), whereas Hap1-KO mice are born at normal weight but display severe failure in body weight gain shortly after birth (5, 10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ainsi, le nombre de sites de recapture du glutamate serait régulé chez la drosophile et les mammifères par la voie de signalisation du récepteur à l'EGF [23]. Des données in vitro sur des cellules PC12 en culture ont montré que la protéine Huntingtine mutée inhibe l'activation de ERK et AKT consécutive à la stimulation du récepteur à l'EGF [24,25]. Nous avons donc fait l'hypothèse que la présence de longues chaînes de résidus glutamine modifierait l'expression de gènes essentiels pour le fonctionnement du système nerveux en altérant, entre autres, la voie de signalisation du récepteur à l'EGF dans les cellules gliales.…”
Section: Les Mécanismes Moléculaires Du Dysfonctionnement Des Astrocytesunclassified